Energy Transfer in Alternative Vehicles - Cieslik, Wojciech (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of research that contributes to a better understanding of energy transfer related to alternative vehicles. The hybridization of power units and alternative propulsion systems are the mainly developed technology in the automotive field today. The modernization of conventional propulsion sources is justified by the increasingly stringent economic, ecological, and comfort requirements. The common link in any renewable energy source or propulsion system today is electric motors. Their correct use in propulsion offers the possibility of reducing or eliminating harmful emissions both in the form of toxic compounds and noise or unwanted vibrations. The research works were related to energy transfer in both hybrid and electric vehicles, and conversion of energy from renewable sources such as photovoltaic installations to power alternative vehicles. However, you will also find in this reprint papers that are related to modules of alternative propulsion such as drivetrain efficiency analysis, ways of energy accumulation in batteries, and influence of the charging method on the energy consumption of a vehicle during its life cycle.